2019
DOI: 10.1080/10717544.2019.1706669
|View full text |Cite
|
Sign up to set email alerts
|

SPA: a peptide antagonist that acts as a cell-penetrating peptide for drug delivery

Abstract: Although cell-penetrating peptides (CPPs) has been proven to be efficient transporter for drug delivery, ideal peptide vectors for tumor therapy are still being urgently sought. Peptide antagonists have attracted substantial attention as targeting molecules because of their high tumor accumulation and antitumor activity compared with agonists. SPA, a derivative of substance P, is a potent antagonist that exhibits antitumor activity. Based on the amino acid composition of SPA, we speculate that it can transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…In our previous study, SPA was shown to have an efficient drug delivery capacity similar to that of cell‐penetrating peptides. The study on the cellular uptake mechanism of SPA demonstrated that SPA could enter cells by destabilizing cell membranes, which is similar to the mechanism of AMPs 18 . Cationicity, hydrophobicity and amphiphilicity are major structural features that affect the antimicrobial activity of AMPs 5 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our previous study, SPA was shown to have an efficient drug delivery capacity similar to that of cell‐penetrating peptides. The study on the cellular uptake mechanism of SPA demonstrated that SPA could enter cells by destabilizing cell membranes, which is similar to the mechanism of AMPs 18 . Cationicity, hydrophobicity and amphiphilicity are major structural features that affect the antimicrobial activity of AMPs 5 .…”
Section: Introductionmentioning
confidence: 84%
“…The peptides used in this study were synthesized in our previous study 18 . The sequences of SP, SPA and L‐SPA are showed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…All peptides and the peptide–CPT conjugate were synthesized as described previously 31 . For the synthesis of FITC‐labeled peptides, the lysine at the C‐terminus to be modified by FITC was incorporated as Fmoc‐Lys (Mtt)‐OH.…”
Section: Methodsmentioning
confidence: 99%
“…FITC was attached to the side chain of the lysine by treating a resin‐bound peptide (0.1 mmol) with FITC (0.15 mmol) and diisopropyl ethyl amine (0.6 mmol) in DMF for 12 h. Peptide with cysteine to serve as N‐terminus were synthesized, where the thiol group was to serve as the attachment site for the cleavable linker. CPT was attached to the cysteine with a disulfide carbonate releasable linker 31 . All crude peptides and conjugate were purified and analyzed by reversed‐phase high performance liquid chromatography (RP‐HPLC) using a C18 column, and then characterized by electrospray ionization mass spectrometry (ESI‐MS).…”
Section: Methodsmentioning
confidence: 99%
“…The 11mer peptide Substance P (SP, RPKPQQFFGLM-NH2) with cell-penetrating properties [108] was modified to obtain the peptide called SPA ([DArg 1 , D-Trp 5,7,9 , Leu 11 ] Substance P) [66]. SPA peptide was further optimized for efficient pDNA delivery by grafting a stearic acid to the N-terminus of the peptide, which enabled complex formation (>200 nm imaged by TEM), cellular internalization, and luciferase expression comparable to LF2000.…”
Section: Sta-spamentioning
confidence: 99%